Greek Philosophy and the Problem of Evil in Clement of Alexandria and Origen - Roig Lanzillotta, Lautaro (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2013)
In spite of the acrimonious criticism issued against it, Greek philosophy always exerted an irresistible attraction to Christian writers of the fi rst centuries. Not only did their censure of divine anthropomorphism, mythology, and polytheism rely on Greek philosophical precedents. Surprisingly, also their attacks against Greek philosophy itself often resorted to philosophical interschool polemics. This paper, however, focuses on the positive and creative side of this appropriation: during the second and third centuries Clement of Alexandria and Origen raised the cultural level of Christian theology by their large use of the Greek philosophical discourse. The present study focuses on how they dealt with the problem of the existence of evil in the context of God’s creation and traces their approach back to Greek philosophical precedents.
Keywords: Theodicy; Greek philosophy; Christianity; Judaism; Apocalypticism